Pulse of Sustainable Development: Tourism in Malawi, the Warm Heart of Africa - Fracasso, Gianluca (2011)
This piece of research focusus on the analysis of tourism development problems and possibilities in one of the poorest countries in the world, Malawi. In the last years the country has attempted to develop ecotourism to mitigate some of its development problems and to access some of the benefits linked with the international tourism business. However various instances of tourism development in the least developed economies presented in past researches have shown that poor developing countries that become international destination often display problems in terms of sustainable development with controversial effects. This work therefore examines the condition and organisation of the tourism industry in Malawi and the implications for sustainable development and ecotourism.